Economic evaluation of Manchester procedure versus sacrospinous hysteropexy: A follow-up analysis of a randomized clinical trial - Sascha F. M. Schulten; Rosa A. Enklaar; Mirjam Weemhoff; Hugo W.F. van Eijndhoven; Sanne A.L. van Leijsen; Eddy M.M. Adang; Kirsten B. Kluivers (PLoS ONE, 2025)
Background Pelvic organ prolapse is a common condition in females. The reported lifetime risk of undergoing pelvic organ prolapse surgery is estimated to affect up to 20% of women. Recently, a higher level of surgical success after the Manchester procedure has been shown compared to sacrospinous hysteropexy. As the costs in healthcare are rising, it is also important to consider the resources and associated cost implications of the choice between these two procedures. An economic evaluation was conducted to compare the alternative costs and benefits. Methods An economic evaluation alongside a randomized controlled trial (RCT) was performed from a societal and healthcare perspective at 2 years of follow-up according to the intention to treat principle. The RCT was a multicenter, randomized, open label trial, executed in 26 Dutch hospitals. 434 women were randomly assigned to the Manchester procedure or sacrospinous hysteropexy. Direct costing data were obtained from electronic case report forms and Medical Consumption Questionnaires. Indirect costing data were obtained by the Productivity Cost Questionnaire. Quality-adjusted Life Years (QALYs) were calculated from the scores on the Euroqol5D-5L questionnaire. Mean cost differences and their 95% confidence intervals (CI) were calculated. Results From the societal perspective, the Manchester procedure was significantly less expensive than sacrospinous hysteropexy, with a mean difference of 1458.34 euros (95% CI −2746.16 to −170.52). There was no significant difference in the number of QALYs gained over period of 2 years between the arms: 1.67 QALYs (95% confidence interval (95% CI) 1.63 to 1.71) for the sacrospinous hysteropexy group and 1.68 QALYs (95% CI 1.65 to 1.72) for the Manchester procedure group (p = 0.346). Conclusions During two years of follow-up the Manchester procedure and sacrospinous hysteropexy showed no statistically significant different effectiveness in terms of QALYs gained against significantly higher costs for sacrospinous hysteropexy.